Microbiological quality of surface waters of Rome and it’s County from 1890 to 2010: a systematic review of Roman Hygiene School - Caterina Palazzo; Riccardo Montacutelli; Rosella Del Vecchio; Angelo Giuseppe Solimini; Lucia Marinelli; Anna Maria Lombardi; Maria De Giusti; Gaetano Maria Fara; Antonio Boccia (Epidemiology, Biostatistics and Public Health)
Research on the quality of surface waters has been erformed in Italy during the development of large urban areas, and in Rome this has been the duty of the Istituto di Igiene of the Sapienza University since 1890. Using MedLine - along with traditional consultation of papers printed before 1968 - we identified 100 articles published in the period from 1890-2010. Thirty of them met the inclusion criteria (to have been written by researchers of Roman universities and to contain microbiological information about the surface waters of Rome). The majority of papers identified (46.6%) were published during the Sixties and Seventies, and 30% in the twenty years that followed (1980-1999). The most frequent microbiological descriptors were “Total coliforms” and “Streptococci”. The body of waters most frequently investigated were the river Tiber and the coastal waters around Fiumicino, where the Tiber flows into the Tyrrhenian sea. The quality of surface waters has always been of central interest to the researchers of the Roman School of Hygiene. The excellent quality of past research, and the renovated interest of International Organizations and of the European Union, should encourage public health researchers to persist in this strategic field of investigation which has strong interconnections with the protection of individual well-being and community health, as well as with environmental preservation.